2021
DOI: 10.3390/jcm10092018
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth Restriction and Subsequent Low Grade Fetal Inflammatory Response Are Associated with Early-Onset Neonatal Sepsis in the Context of Early Preterm Sterile Intrauterine Environment

Abstract: There is no information about whether fetal growth restriction (FGR) is an independent risk factor for low-grade fetal inflammatory response (FIR), and which is more valuable for the prediction of early-onset neonatal sepsis (EONS) between low-grade FIR or fetal inflammatory response syndrome (FIRS) in the context of human early preterm sterile intrauterine environment. We examined FIR (umbilical cord plasma (UCP) CRP concentration at birth) according to the presence or absence of FGR (birth weight < 5th pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…It has been found that there is an interplay between the blood glucose level of patients with sepsis and the development of the disease. Specifically, high blood sugar levels may aggravate inflammatory responses and impair the body's resistance, thereby accelerating disease development [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that there is an interplay between the blood glucose level of patients with sepsis and the development of the disease. Specifically, high blood sugar levels may aggravate inflammatory responses and impair the body's resistance, thereby accelerating disease development [ 21 ].…”
Section: Discussionmentioning
confidence: 99%